Penerapan Aplikasi Quizizz dalam Pembelajaran Matematika untuk Meningkatkan Minat dan Motivasi Belajar Siswa - Sudianto, Sudianto; Sri Mulyani Nurfazriyah (Papanda, 2025)
The low student interest and motivation in learning are among the contributing factors to poor academic achievement. One potential solution to address this issue is the integration of digital technology based on game-based learning, such as the Quizizz application. This study aims to examine the impact of using Quizizz on improving students' interest and motivation in learning mathematics through a Systematic Literature Review (SLR) approach. The SLR process includes identifying the research focus and questions, searching for relevant articles, selecting articles based on specific criteria, and analyzing the selected studies. Data were collected from various journal articles published between 2019 and 2025, accessed through Google Scholar, Search, Garuda, and other databases, using predetermined inclusion criteria. The analysis results show that the use of Quizizz consistently has a positive impact on mathematics learning. The application not only facilitates access to quiz questions but also creates a fun and interactive learning environment. Moreover, Quizizz has been proven to enhance content mastery, promote active student engagement, and strengthen learning motivation. Therefore, Quizizz can be considered an effective alternative digital learning medium for increasing student interest, motivation, participation, conceptual understanding, and engagement in mathematics education.